Pengembangan Media Layanan Informasi Berbabis Website Untuk Stres Akademik Siswa - Nindi Arlena; Akhmad Fajar Prasetya (Program Studi Bimbingan dan Konseling, FKIP Universitas Pancasakti Tegal, 2022)
This study aims to find out the feasibility of website-based information service media for academic stress on students. This type of research is R&D (Research and Development) with the Brog and Gall method. This development model is only up to the product revision stage only. Preliminary studies spread the instrument to students, and supported by the results of interviews with BK teachers. The study subjects of 34 students of class X Tatabusana 2 SMK N 2 Sewon Bantul showed that there are still many students who know about academic stress. The results of this development are measured based on the distribution of expert materi tests and media expert tests. The results of the material expert test assessment get an award of 82.5 with the category of Excellent. While the Media Expert Test gets a score of 75 with a Good category. Overall polling results with an average score of 78.8 with excellent category. Based on these results, the Development of Website-Based Information Service Media For Academic Stress of Students at SMK N 2 Sewon Bantul Yogyakarta Is Suitable for use. Key: Information Services, Academic Stress, websites.